KURIKULUM LAMA VS KURIKULUM BARU: TANTANGAN DAN PELUANG DALAM PEMBELAJARAN SD - Anto, Sumianto; Yonita, Lutfiah Tul Jannah; Miranda, Miranda; Sarah, Nur (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2025)
The curriculum shift in Indonesia from the 2013 Curriculum to the Merdeka Curriculum has significantly impacted teaching practices in primary schools. This study aims to describe the differences in implementation between the two curricula and to identify the challenges and opportunities faced by teachers during the learning process at UPT SDN 003 Bangkinang Kota. A descriptive qualitative method was used, with data collected through classroom observations in Grade IV and in-depth interviews with the homeroom teacher. The findings reveal that the Merdeka Curriculum is more flexible, student-centered, and emphasizes contextual and project-based learning, in contrast to the more structured and teacher-centered 2013 Curriculum. While teachers feel more freedom in designing lessons, they also face challenges such as readiness to teach, limited facilities, and time management. Nevertheless, the Merdeka Curriculum offers great potential for increasing student engagement, creativity, and character development through the Profile of Pancasila Students. In conclusion, the Merdeka Curriculum shows positive potential in enhancing the quality of learning, but its success requires consistent support and guidance for teachers and schools. Keywords : Curriculum 2013, Merdeka Curriculum, Challenges, and Opportunities